The Effect of Self-efficacy on Sustainable Development: The PetroMasila in Yemen - Al-Zubaidi, Razi; Ariffin, Mohd Khairol Anuar Bin Mohd; Abdulsamad, Akram; Raqee, Ali; Ismail, Mohd Idris Shah; Ahmad, Kamarul Arifin (Advances in Social Sciences Research Journal, 2022)
This research addresses the mechanism that the components of self-efficacy impact the sustainable development efficacy among employees of PetroMasila in Yemen. The methodology of the current study was quantitative. The online questionnaire was utilized to collect data from 342 employees who are working in the department of project management. The data analysis was conducted by the Structural Equation Model (SEM) in Smart-PLS Software. The findings of this study indicated that all components of self-efficacy, namely past performance, vicarious experiences, verbal persuasion, and emotional cues, have a significant and positive influence on the oil industry’s sustainable development effectiveness. The model of research explained 45% of the whole variance in sustainable development efficacy. Furthermore, this study discusses the limitation and future studies.